Communication Strategy of KPPBC TMP B Balikpapan In Instagram Account : @pojok.inspirasi.bpn Personification As A Strategy “Remaja Hobi Ngopi” - Darmadi Joko Sumarah; Pawito Pawito; Albert Muhammad Isrun Naini (International Journal of Science and Applied Science: Conference Series, 2022)
The low level of media literacy in Indonesian society, especially in the sphere of social media, coupled with the emergence of a pessimistic view of the Government’s public communication, demands changes to the Government’s social media accounts. KPPBC TMP B Balikpapan, the representative of the Government, found the same condition and tried to find the answer. This study aims to explain digital communication policies carried out in social media. In-depth interviews were conducted with key informants to reveal insights into the communication phenomenon under study. The result of this study state that the digital communication policy implemented by KPPBC TMP B Balikpapan is a branding strategy through the personification of “Remaja Hobi Ngopi.” The personification of teenagers who like drinking coffee has the power of a friendly and open impression on the community.